Optical control of spin textures in quasi-one-dimensional polariton condensates - Antón, C. (2015)
We investigate spin transport through polarization-resolved spectroscopy by propagating polariton condensates in a quasi-one-dimensional microcavity ridge along macroscopic distances. Under circularly polarized, continuous-wave, nonresonant excitation, a sinusoidal precession of the spin in real space is observed whose phase depends on the emission energy. The experiments are compared with simulations of the spinor-polariton condensate dynamics based on a generalized Gross-Pitaevskii equation, modified to account for incoherent pumping, decay, and energy relaxation within the condensate.